International Handbook of Language Acquisition 2019
DOI: 10.4324/9781315110622-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Robotic Models of Early Language Development

Abstract: We review computational and robotics models of early language learning and development. We first explain why and how these models are used to understand better how children learn language. We argue that they provide concrete theories of language learning as a complex dynamic system, complementing traditional methods in psychology and linguistics. We review different modeling formalisms, grounded in techniques from machine learning and artificial intelligence such as Bayesian and neural network approaches. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Computational analyses suggest that self-directed sampling can vastly simplify the task of learning new words and categories under uncertainty, as long as learners employ strategies that increase the frequency of word meanings that have higher uncertainty (Hidaka et al, 2017;Oudeyer, Kachergis, & Schueller, 2019;Settles, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Computational analyses suggest that self-directed sampling can vastly simplify the task of learning new words and categories under uncertainty, as long as learners employ strategies that increase the frequency of word meanings that have higher uncertainty (Hidaka et al, 2017;Oudeyer, Kachergis, & Schueller, 2019;Settles, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to our knowledge, none of the existing models for joint segmentation, meaning acquisition, and subword unit learning have been tested with real naturalistic input available to language learning infants (see also [5]). Instead, the models (or robots) have used supervised phone recognizer front-ends [12,13,27], or simplified enacted high-quality caregiver speech (e.g., using CAREGIVER corpus [28], as in [14][15][16][17]).…”
Section: Introductionmentioning
confidence: 99%
“…Computational modeling, on the other hand, enables evaluation of theories and models while considering multiple aspects of the learning process simultaneously (see [5] for a recent overview). In this respect, previous models have shown that fully unsupervised acoustic word discovery is challenging due to the variable nature of acoustic speech, even though some recurrent patterns are still learnable (e.g., [6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…For studies exploring the contribution of the visual modality, we will refer to Alishahi and Fazly (2010) for models operating on image/caption pairs, or and Nikolaus et al (2022) for models operating on videos -see also Chrupała (2022) for a recent review. Similarly, embodied or socially grounded language learning agents have been proposed in Yu and Ballard (2003), Hermann et al (2017), Lair et al (2019), andOudeyer et al (2019).…”
Section: The Environment Model: From What Is Language Learned?mentioning
confidence: 99%